PENGEMBANGAN MEDIA PEMBELAJARAN KOTAK KARTU MISTERI PADA MATERI MENULIS DESKRIPSI KELAS IV SEKOLAH DASAR - Putri Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research and development aim to develop and determine the feasibility of the Mystery Card Box as a learning medium based on expert validation and product trials, specifically for teaching Indonesian language in fourth grade of elementary school with a focus on descriptive writing skills. The method used in this study is Research and Development (RnD), utilizing the ASSURE development model and employing validity tests which include media, material, and language validation using a Likert scale questionnaire instrument. The results showed an average percentage score of 90% obtained from media, material, and language expert evaluations. The product trials were conducted with fourth grade students at SDN Pondok Pinang 01 Pagi, Kebayoran Lama, South Jakarta. The product trials achieved an average percentage score of 98%, covering individual trials, small group trials, and field trials. There was an improvement in students’ descriptive writing skills, with an average learning outcome increase of 12%.